An Integrated Understanding of the Rapid Metabolic Benefits of a Carbohydrate-Restricted Diet on Hepatic Steatosis in Humans - Mardinoglu, Adil; Wu, Hao; Bjornson, Elias; Zhang, Cheng; Hakkarainen, Antti; Räsänen, Sari M.; Lee, Sunjae; Mancina, Rosellina M.; Bergentall, Mattias; Pietiläinen, Kirsi H.; Söderlund, Sanni; Matikainen, Niina; et al. (Cell metabolism, 2018)
A carbohydrate-restricted diet is a widely recommended intervention for non-alcoholic fatty liver disease (NAFLD), but a systematic perspective on the multiple benefits of this diet is lacking. Here, we performed a short-term intervention with an isocaloric low-carbohydrate diet with increased protein content in obese subjects with NAFLD and characterized the resulting alterations in metabolism and the gut microbiota using a multi-omics approach. We observed rapid and dramatic reductions of liver fat and other cardiometabolic risk factors paralleled by (1) marked decreases in hepatic de novo lipogenesis; (2) large increases in serum β-hydroxybutyrate concentrations, reflecting increased mitochondrial β-oxidation; and (3) rapid increases in folate-producing Streptococcus and serum folate concentrations. Liver transcriptomic analysis on biopsy samples from a second cohort revealed downregulation of the fatty acid synthesis pathway and upregulation of folate-mediated one-carbon metabolism and fatty acid oxidation pathways. Our results highlight the potential of exploring diet-microbiota interactions for treating NAFLD. [Display omitted] •A low-carbohydrate diet (LCD) improves liver fat metabolism in NAFLD patients•The LCD promotes rapid shifts in the gut microbiota composition of NAFLD patients•The LCD-induced microbial changes are associated with increased circulating folate•The LCD increases folate-dependent one-carbon metabolism gene expression in liver Mardinoglu et al. use multi-omics to investigate the effects of a carbohydrate-restricted diet in obese NAFLD patients. They show that the diet improves liver fat metabolism, promotes rapid shifts in the gut microbiota, increases circulating folate, and upregulates expression of genes involved in folate-dependent one-carbon metabolism in the liver.